Subject Index to Volume 82. (Journal of Singing)
The document provides a comprehensive overview of recent scholarship and professional discourse in voice pedagogy, vocal health, voice science, performance, and related fields as presented in the Journal of Singing. It includes studies on voice acoustics and formant tuning, vocal health issues such as vocal neuropathy and hydration practices, pedagogical approaches including mentorship and culturally responsive repertoire, and explorations of voice science principles like breathing and vibrato. Additionally, it features interviews with performers, discussions on collaborative pianists, and reviews of vocal literature and music resources. This collection serves as a resource for researchers and practitioners seeking current, evidence-based perspectives on singing and voice education.